The Factors Affecting Land Prices In Housing Location In Sidoarjo Regency - Partomi Simangunsong; Arasy Alimudin; Muh. Barid Nizaruddin Wajdi (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2017)
The need for residential location is one of the basic needs of the community and the attractiveness of the residential location is a unique feature where this feature is not made by the respective occupants, but by external factors from the residential environment in the area. This study aims to analyze the factors that are considered as the basis that affect the price of land. This research uses quantitative approach with associative research method. Linear analysis with quadratic method. Ordinary Least Square (OLS). From the analysis of this research model obtained log-linear F-accounting 70,162 while the value of F-table (0,05; 5,48) is 2,45. because F-count> F-table, Ho means rejected and explanatory variables include Distance to city center, Distance to main road, Distance to toll gate, Road width, and security simultaneously can be explained significantly at land sale price.